Natural Resources and Conflicts: Theoretical Flaws and Empirical Evidence from Northern Kenya - Dietz, T.; Adano, W. R.; Witsenburg, K. (Africa Environmental Review Journal, 2015)
The Horn of Africa is viewed as a battleground of violent conflicts which are prompted by growing resource scarcity with population increase. Such conflicts are argued to be particularly violent in poor regions where many ethnic groups have to compete for scarce natural resources and where people hardly have the capacity to develop adaptable and ingenuous approaches to avoid or resolve conflicts. This paper tests the validity of such claims using analyses of a long-term data of inter-ethnic conflicts and associated incidents of loss of livestock to raids, banditry attacks and killings between pastoral communities in Marsabit District, Northern Kenya. The analysis is strengthened using case studies of access to a severely scarce water resources in rural Kenya, and even more so in pastoral areas. The herders escape local drought effects by moving herds to places where potential loss of livestock is anticipated to be less severe. The poor herdsmen, for whom transhumance is not affordable, are left behind in drought areas. According to the herders, it is more rational to cooperate with people from different ethnic groups in times of drought in order to share the scarce water resources. This view was also supported by the yearly statistics on violence which show that twice as many deaths occurred in wet years than in drought years. We find no evidence neither that violence is increasing in relative terms, nor that ethnic violence is related to environmental scarcity. On the whole, the study cannot verify the assumption that increasing competition over scarce resources on Marsabit Mountain results in more ethnic violence. In particular, water resources seem to play a vital role in social interaction, reconciliation, sharing and cooperation in survival strategies. The result shows how important conflict-avoiding institutions are in societies which have learned how to deal with scarcity by century-old experiences in hardship areas. These conflict-avoiding institutions are shaped and reshaped through time, subjected as they are to natural hardship, external stress, modernity and technological change.